Weekly training load in elite male ice hockey: practice versus competition demands - Rago, V.; Muschinsky, A.; Deylami, K.; Mohr, M.; Vigh-Larsen, J. F. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The aim of this study was to compare training load (TL) between practice and games across in-season microcycles in elite Danish male ice hockey.